2020
DOI: 10.1590/0103-6564e180023
|View full text |Cite
|
Sign up to set email alerts
|

Doença de Alzheimer: a experiência única de cuidadores familiares

Abstract: Resumo A demência é uma síndrome de curso lento, progressivo e de natureza crônica, sendo o subtipo doença de Alzheimer (DA) a mais comum. Muitos estudos são realizados a partir das demandas da pessoa com demência, porém na perspectiva do cuidador eles são escassos. A pesquisa qualitativa teve como objetivo conhecer aspectos singulares da experiência do cuidar na perspectiva de cuidadoras familiares de idosos com DA, a partir de abordagem qualitativa. Foi utilizado o método fenomenológico proposto por Giorgi e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
4
0
14
Order By: Relevance
“…However, we note that this reconstruction process also entails a positive facet despite the burdensome negative aspects. The family caregivers composing other studies’ samples,( 11 , 21 ) also reported specific beneficial changes in their lives resulting from providing care.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, we note that this reconstruction process also entails a positive facet despite the burdensome negative aspects. The family caregivers composing other studies’ samples,( 11 , 21 ) also reported specific beneficial changes in their lives resulting from providing care.…”
Section: Discussionmentioning
confidence: 86%
“…( 9 , 10 ) However, few studies address family caregivers during the care process, especially emphasizing anticipatory grief. ( 11 ) Hence, there is an important gap in the scientific literature, considering that grief encompasses a set of responses raised by a significant loss, not necessarily caused by death, and anticipatory grief is triggered by the progressive threat of loss. ( 12 ) Another evident gap is that studies seldom address coping strategies adopted by family caregivers to facilitate the care provided to bedridden elderly patients affected by chronic degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Outrossim, pacientes acometidos com tal patologia, apesar de na maior parte do tempo serem cuidados pelos profissionais da saúde do Instituto onde estão, são também cuidados por seus familiares, os quais podem cuidar por curto ou longo período e, com isso, sofrem demasiadamente com os efeitos psicologicamente nocivos que a doença causa. Mattos & Kovács (2020) discutem a dolorosa e solitária experiência do cuidar de um ente com Alzheimer, tendo esses que muitas vezes suprimir os sentimentos de angústia e impotência frente a uma doença evolutiva e degenerativa, o qual deixa o doente ainda mais dependente e o cuidador mais desolado.…”
Section: Resultsunclassified
“…O estudo realizado com cuidadores familiares participantes dos grupos da Universidade de São Paulo demonstrou em seus achados, que as cuidadoras se interessaram na busca e acesso aos grupos de apoio psicoeducacional da Associação Brasileira de Alzheimer como possibilidade de troca de experiências e orientação no manejo dos sintomas da DA (13) . (14) .…”
Section: Introductionunclassified